The Use of Language Variations by Native Arabic Speakers in Learning Process at University in Indonesia: A Narrative Inquiry Study - Syafni, Hafidhah; Mustofa, Syaiful; Rusuly, Usfiyatur (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
The learning of Arabic language in Indonesia heavily relies on the role of native speakers, who incorporate linguistic variations into classroom interactions. This article aims to explore the experiences of native Arabic-speaking lecturers in selecting and using language variations during the teaching process at UIN Malang, Indonesia. It also compares these strategies with past teaching practices in their home countries and then examines their perspectives on the future direction of Arabic language education. In this study, the researcher used a qualitative approach with a narrative inquiry method that emphasizing an individual's story or life experience as the primary data in the research. The research data collection technique uses a narrative frame and interviews. To analyse the data, the researcher used the following steps: 1) data collected through narrative frame and interviews, 2) selected and categorized the information to simplify its presentation, 3) the data was presented by organizing the classified information based on the lecturers' teaching experiences which following a temporal pattern, 4) drawing conclusions. The results showed that: 1) Fusha (Modern Standard Arabic) is prioritized in education for its clarity, consistency, and universal comprehension, despite the daily use of ‘Amiyah (Colloquial Arabic). 2) Native Arabic-speaking lecturers adapt their teaching in Indonesia by simplifying Fusha but strictly avoid Indonesian, emphasizing full Arabic immersion for effective learning. 3) Arabic language education continues to emphasize Fusha to ensure linguistic integrity, effective communication, and standardized learning, especially in Indonesia.